The physiological impact of soccer on elite female players and the effects of active recovery training - Andersson, H. M. (Örebro University, School of Health and Medical Sciences, 2010)
Female soccer is becoming more popular and professional in the world. There are, however, limited scientific data available on how elite female players respond to physical stress during soccer games. An effective recovery strategy following a game is important, because there are few recovery days between the games in international tournaments. The present thesis, which was designed to mirror a competitive situation, aimed to investigate changes in several physiological systems occurring in female elite players in response to two soccer games. It also aimed to investigate the effects of active recovery training on the recovery of several physiological systems. METHODS: Two elite female soccer teams played two 90-min games separated by 72 h active or passive recovery. The active recovery training (cycling at 60% HRpeak, resistance training at <50% 1RM) lasted one hour and was performed 22 and 46 h after the first game. Countermovement jump (CMJ), 20-m sprint time and isokinetic knee strength were measured before, immediately, 5, 21, 45, 51, and 69 h after the first game, and immediately after the second game. The physical stress markers (CK, urea), oxidative stress markers (e.g., GSSG, lipid peroxidation), endogenous (e.g., UA, thiols) and dietary antioxidants (e.g., tocopherols, carotenoids) and a large battery of cytokines (e.g., IL-6, TNF-?) were analysed in blood. RESULTS: No significant differences were observed in the performance parameters, oxidative stress and antioxidant levels or inflammatory response between the active and passive recovery groups. Sprint and isokinetic knee strength were reduced by the same extent after both games. CMJ decreased after the first game and remained reduced throughout the study period. Blood physical stress markers, GSSG and endogenous antioxidants increased with similar amplitude after both games together with unchanged lipid peroxidation. The dietary antioxidants showed either a rapid and persistent change (e.g., tocopherols) or a delayed rise (carotenoids) after the first game. A transient increase occurred in several pro- (e.g., IL-12, TNF-a, MCP-1), anti-inflammatory (e.g., IL-4, IL-10, INF-a) and mixed (IL-6) cytokines after the first game. Fewer cytokines increased in response to the second game. CONCLUSION: Two repeated elite female soccer games separated by 72 h induced similar acute changes in several physiological parameters. After the first game, differences in the recovery pattern of the neuromuscular parameters occurred. In particular, the slow recovery of CMJ indicates that special attention should be devoted to the training of explosive force. Furthermore, the recruitment of antioxidants in response to the transient increase in GSSG resulted in the maintenance of the redox-balance in female players. Similarly, a strong and balanced pro- and anti-inflammatory cytokine response occurred after one single female soccer game. The consequences of the dampened cytokine response during repeated soccer games are, however, unknown. In general, the majority of the parameters had recovered prior to the second game and the physiological alterations induced by the first game did not affect the performance of players in the second game. Finally, active recovery training conducted after a soccer game does not accelerate the recovery time for neuromuscular, oxidative stress, antioxidant and inflammatory responses in elite female players.